Exploring teaching writing techniques and strategies of secondary school English teachers: a case study / Suhana Ahmad - Ahmad, Suhana (2014)
This study aimed at investigating teaching techniques and strategies followed by the English language teachers in a secondary school concerning writing practice inside the classroom. It also aimed at identifying the problems faced by the English language teachers in teaching writing. Previous researches have reported that most first year students at the local universities do not meet the requirement for writing skills in the English language. Despite the eleven years of formal teaching and learning of the English language in both primary and secondary schools, the students still do not master the required skills to help them at the university level. So, the study attempts to investigate the real situations in the secondary writing classrooms. The sample of the study consisted of four English language teachers who teach Form Four and Form Five students in a secondary school chosen to fit the purpose of the study. The instruments of the study were teacher interviews and classroom observations of writing lessons. Also, a set of questionnaire was developed based on a similar previous study for data triangulation purposes. Findings from the study show that process writing is the most dominant teaching writing technique demonstrated by the respondents. Shared task, on the other hand, is the most preferred teaching writing strategies among the teachers. Recommendations were also drawn out at the end of the study.